Pengaruh Kompensasi, Motivasi dan Komitmen Organisasi Terhadap Kinerja Karyawan pada PT Nuroho Software Consulting Surabaya - Yulia Sugianti; Eka Farida; Ita Athia (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine and analyze the effect of compensation, motivation, and organizational commitment on employee performance at PT Nuroho Software Consulting Surabaya. The type of approach taken is a quantitative approach. With this type of research explanatory research. The sample used in this study were 71 employees using a saturated sample. The data analysis method used in this study is multiple linear regression analysis. Testing the data used is testing the simultaneous hypothesis (Test F) and testing the partial hypothesis (Test t). The research results show that compensation partially affects the performance of employees at PT Nuroho Software Consulting Surabaya. Motivation partially does not affect employee performance at PT Nuroho Software Consulting Surabaya. Organizational commitment has no effect on employee performance at PT Nuroho Software Consulting Surabaya. While simultaneously compensation, motivation and organizational commitment have a significant effect on employee performance at PT Nuroho Software Consulting Surabaya. Keywords:Compensation, Motivation, Organizational Commitment and Employee Performance